2022
DOI: 10.1007/s40843-021-1935-5
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Sr2Fe1.5Mo0.5O6−δ with Sc as a new single-phase cathode for proton-conducting solid oxide fuel cells

Abstract: Sc-doped Sr 2 Fe 1.5 Mo 0.5 O 6−δ (SFMSc) was successfully synthesized by partially substituting Mo in Sr 2 Fe 1.5 -Mo 0.5 O 6−δ (SFM) with Sc, resulting in a higher proton diffusion rate in the resultant SFMSc sample. Theoretical calculations showed that doping Sc into SFM lowered the oxygen vacancy formation energy, reduced the energy barrier for proton migration in the oxide, and increased the catalytic activity for oxygen reduction reaction. Next, a proton-conducting solid oxide fuel cell (H-SOFC) with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 68 publications
0
30
1
Order By: Relevance
“…One is at the Fe site next to the P cation (Fe–P site), and the other is at the Fe site far from the P cation (Fe–Fe site), as shown in Figure S4. The O 2 adsorption energies were calculated at 0.27 and 0.52 eV on the Fe–P and Fe–Fe sites, respectively, implying O 2 adsorption on the Fe–P site is more favorable at the LSFP surface due to the lower energy 44–46 . The analysis of the charge density difference (Figure 2C) revealed that the P‐doping into LSF evidently changes the electronic structure of the Fe ions next to the P cation (Fe–P site), leading to a charge depletion for the Fe ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One is at the Fe site next to the P cation (Fe–P site), and the other is at the Fe site far from the P cation (Fe–Fe site), as shown in Figure S4. The O 2 adsorption energies were calculated at 0.27 and 0.52 eV on the Fe–P and Fe–Fe sites, respectively, implying O 2 adsorption on the Fe–P site is more favorable at the LSFP surface due to the lower energy 44–46 . The analysis of the charge density difference (Figure 2C) revealed that the P‐doping into LSF evidently changes the electronic structure of the Fe ions next to the P cation (Fe–P site), leading to a charge depletion for the Fe ions.…”
Section: Resultsmentioning
confidence: 99%
“…The O 2 adsorption energies were calculated at 0.27 and 0.52 eV on the Fe-P and Fe-Fe sites, respectively, implying O 2 adsorption on the Fe-P site is more favorable at the LSFP surface due to the lower energy. [44][45][46] The analysis of the charge density difference (Figure 2C) revealed that the P-doping into LSF evidently changes the electronic structure of the Fe ions next to the P cation (Fe-P site), leading to a charge depletion for the Fe ions. The charge depletion could result in the increase of the Fe valence (loss of electrons).…”
Section: Resultsmentioning
confidence: 99%
“…The peak at around 531.8 eV is attributed to hydroxyl groups or carbonate adsorbed on the surface. The result manifests that a high amount of oxygen vacancies has been likely produced (O ads /O lat = 1.86), which is expected to accelerate the transport of oxygen ions and improve the ORR activity of the cathode [2,32].…”
Section: Xps and Tg Analysismentioning
confidence: 99%
“…The peaks of 779.7 and 795.0 eV are assigned to Ba 2+ in the perovskite or the surface carbonate [34]. Two sets of peaks belonging to Co 4+ (2p 3/2 at around 781.3 eV and 2p 1/2 at around 797.0 eV) and Co 3+ (2p 3/2 at around 777.8 eV and 2p 1/2 at around 793.0 eV) are obtained by deconvolution [31][32][33][34][35][36]. Two weak satellite peaks are attributed to Co 3 O 4 (a mixed state of Co 2+ and Co 3+ ), indicating a small amount of Co 2+ is on the surface of the BGPC sample [37,38].…”
Section: Xps and Tg Analysismentioning
confidence: 99%
“…35–37 However, single-phase cathodes with triple-conduction, namely oxygen-ion conduction, proton-conduction, and electron-conduction, have been proposed in recent years and are claimed to extend TPBs to the whole cathode surface and thus improve the cathode performance. 38–40 It is known that many triple-conduction cathodes are derived from proton-conducting oxides. 41 This design is reasonable based on the consideration that the proton-conducting oxide as the parent compound can maintain some proton conduction for the derived cathode, and the addition of transition metals into the proton-conducting oxide can introduce electronic conduction and catalytic activity.…”
mentioning
confidence: 99%